Assessment of morphological mhanges of Taleghan river in upstream of Taleghan dam - Somaiyeh Khaleghi; Seyyed Hasan Sadogh; Mahnaz Khodayari (Sustainable Earth Trends)
River channels have been affected by climate changes and human interventions such as channelization, dam, gravel and sand mining and land use changes. Dam changes water and sediment transport in river systems. These changes are as one of the most important factors affecting upstream and downstream river morphology. The aim of this paper is to explain the effect of Taleghan dam (it was constructed from 2001-2006) on upstream of Taleghan River over the period 2000–2017. Taleghan River is very important river in the Central Alborz of Iran. For this reason, Taleghan River was divided 2 reaches as control reach and backwater reach. Channel morphology have been investigated using historical aerial photographs, remote sensing images and field observations. Also channel width, sinuosity index, and particle size distribution were calculated for two reaches pre and post-dam construction. Results showed that the channel width was increased in the post-dam period. Widening was dominated in the backwater and the control reaches but increasing in the channel width in the backwater reach is more than the control reach.  the channel width has been increased due to the impact of the dam and flood events. Also the results of grain size distributions showed that dam affects the grain size distribution and leads to an increase in the fine particle size. Finally, the channel adjustment (aggradation and widening) in upstream of Taleghan River may cause floodplain inundation and damage to agriculture and residential area in floodplain